2008
DOI: 10.1371/journal.pone.0001891
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Induced Tolerance towards Antimicrobial Peptides

Abstract: Increased tolerance to antimicrobial agents is thought to be an important feature of microbes growing in biofilms. We address the question of how biofilm organization affects antibiotic susceptibility. We established Escherichia coli biofilms with differential structural organization due to the presence of IncF plasmids expressing altered forms of the transfer pili in two different biofilm model systems. The mature biofilms were subsequently treated with two antibiotics with different molecular targets, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 65 publications
2
60
0
Order By: Relevance
“…Pseudomonas aeruginosa biofilms showed a reduced susceptibility when challenged with the antimicrobial agent colistin, and it was suggested that the enhanced resistance is due to the development of a tolerant subpopulation in the biofilm. The resistance mechanisms also were linked to the adaptation or activation of a surviving phenotype, targeting physiological mechanisms, and mutations (3,9,29). Kubota and coworkers reported the increased resistance of Lactobacillus plantarum JCM 1149 biofilms to organic acids and concluded that biofilms are protected by extracellular polymeric secretions, and the three-dimensional structure of the biofilm then protects the cells inside the biofilm matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa biofilms showed a reduced susceptibility when challenged with the antimicrobial agent colistin, and it was suggested that the enhanced resistance is due to the development of a tolerant subpopulation in the biofilm. The resistance mechanisms also were linked to the adaptation or activation of a surviving phenotype, targeting physiological mechanisms, and mutations (3,9,29). Kubota and coworkers reported the increased resistance of Lactobacillus plantarum JCM 1149 biofilms to organic acids and concluded that biofilms are protected by extracellular polymeric secretions, and the three-dimensional structure of the biofilm then protects the cells inside the biofilm matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that bacterial cells in biofilms or cells artificially entrapped in a matrix are more resistant to environmental stresses (e.g., antimicrobial substances, heavy metals, toxic chemicals, organic acids, etc.) than their planktonic or freely swimming counterparts (7,9,16,19,29,40). There has been growing interest in recent years in the exploitation of these robust catalysts for biotechnological applications (e.g., biotransformations) to produce value-added chemicals (10,11,12,27).…”
mentioning
confidence: 99%
“…For instance, the increased survival of E. coli biofilms when treated with colistin is not related directly with biofilm forming ability, but rather to the organization of the biofilm (Folkesson et al 2008). Also, there is some evidence that biofilm formation in E. coli induces tolerance to AMPs due to changes in intra-biofilm physiochemical gradients (Folkesson et al 2008).…”
Section: Biofilm Resistance To Antimicrobial Peptidesmentioning
confidence: 99%
“…Biofilms can tolerate up to 1,000 times more antibiotics and disinfectants than their planktonic counterparts (2,7,8). For example, Folkesson et al (12) reported that biofilm formation of E. coli K-12 increases its tolerance to polymyxin E, a polypeptide antibiotic that kills Gram-negative bacteria by disrupting membranes (34,40). Since biofilms are involved in 80% of human bacterial infections (1), it is necessary to study biofilm inhibition and dispersion by AMPs.…”
mentioning
confidence: 99%